2014
DOI: 10.1177/1049909114523825
|View full text |Cite
|
Sign up to set email alerts
|

A Structured End-of-Life Curriculum for Neonatal–Perinatal Postdoctoral Fellows

Abstract: Death in tertiary care neonatal intensive care units is a common occurrence. Despite recent advances in pediatric palliative education, evidence indicates that physicians are poorly prepared to care for dying infants and their families. Numerous organizations recommend increased training in palliative and end-of-life care for pediatric physicians. The purpose of this study is to develop a structured end-of-life curriculum for neonatal-perinatal postdoctoral fellows based on previously established principles an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 64 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…55 The dedicated time in the speciality is probably of most relevance, though this strategy requires a well-coordinated schedule taking into account other parallel rotations, and sometimes, extra-hours work for trainees and faculty. 56 Despite possible benefits of simulation training 57,58 , this strategy was not found in any studies of this review. For instance, one recent controlled study compared simulation training to didactic education on communication skills and difficult discussions, but with some contents on symptom management, in paediatric fellows.…”
Section: Discussionmentioning
confidence: 91%
“…55 The dedicated time in the speciality is probably of most relevance, though this strategy requires a well-coordinated schedule taking into account other parallel rotations, and sometimes, extra-hours work for trainees and faculty. 56 Despite possible benefits of simulation training 57,58 , this strategy was not found in any studies of this review. For instance, one recent controlled study compared simulation training to didactic education on communication skills and difficult discussions, but with some contents on symptom management, in paediatric fellows.…”
Section: Discussionmentioning
confidence: 91%
“…For the pediatric PC specialist familiar with neonatal-perinatal care, this will not necessarily pose concerns. However, for those unfamiliar with neonatal-perinatal care (e.g., a pediatric oncologist who has been trained in PC, or a family physician now boarded in Hospice and Palliative Medicine) there may be a learning curve to ramp up capabilities to address the often unique aspects of pregnancy and childbirth complicated by life-limiting conditions [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…These developments will impose the need for expanded perinatal counseling and open doors for PC clinicians to join neonatologists, geneticists, and maternal-fetal medicine specialists in contributing to perinatal and neonatal decision-making. Already, we see the possibility of expanded genome-wide newborn screening being proposed in the care of all newborns, and even if this is constrained to symptom-driven circumstances, the need to address prognostic uncertainty will call upon the superlative communication skills of trained and informed neonatologists and PC clinicians [ 37 , 38 , 39 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asplin's group in Sweden found that women decided to terminate a pregnancy based on the severity of the malformation. They also indicated that socioeconomic considerations and the doctor at the fetal care unit influenced the decision(20).Other advances in perinatal palliative care have involved the development of a structured end-of-life curriculum for neonatal-perinatal postdoctoral fellows(21) and studying the various perceptions of health care workers regarding perinatal palliative care(22)(23)(24).…”
mentioning
confidence: 99%